In the shadow of the sword : the birth of Islam and the rise of the global Arab empire - Holland, Tom (New York : Anchor Books, 2013)
In the 6th century AD, the Near East was divided between two venerable empires: the Persian and the Roman. A hundred years on, and one had vanished forever, while the other seemed almost finished. Ruling in their place were the Arabs: an upheaval so profound that it spelled, in effect, the end of the ancient world. In The Shadow of the Sword, Tom Holland explores how this came about. Spanning Constantinople to the Arabian desert, and starring some of the most remarkable rulers who ever lived, he tells a story vivid with drama, horror and startling achievement
Introduction. Known unknowns -- Jahiliyya. Iranshahr -- New Rome ; The children of Abraham ; Countdown to apocalypse -- Hijra. More questions than answers ; The forging of Islam -- Envoi : plus c̨a change? -- Timeline -- Dramatis personae
Originally published: London : Little, Brown, 2012
Includes bibliographical references (p. 481-507) and index
Keywords: Islam -- History; Islamic Empire -- History; History